FENOMENA AUDIT DELAY: FINANCIAL DISTRESS PASCA COVID-19 - Mardjono, Enny Susilowati; Astutie, Yanti Puji (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2022)
This study aims to examine the impact of financial distress on audit delay pre-COVID-19 period and firm size, profitability and reputation of audit firms as control variables. The population used in this study are manufacturing companies in the Indonesia Stock Exchange 2018-2020 with a total sample of 189 samples. Sampling is based on a purposive sampling method with certain criteria. Panel data regression analysis is used in the study. The results showed that Audit delay increased in the pre-COVID-19 period than in Post COVID-19 period. The Finacial distress has a significant positive effect on audit delay in the pre-COVID-19 period. Meanwhile, all control variables such as type of audit firms, profitability and reputation of audit firms have negative effects on audit delay pre-COVID-19 period.